In Vitro Assembly and Stabilization of Dengue and Zika Virus Envelope Protein Homo-Dimers - Stefan W. Metz; Emily N. Gallichotte; Alex Brackbill; Lakshmanane Premkumar; Michael J. Miley; Ralph Baric; Aravinda M. de Silva (Scientific Reports, 2017)
Abstract Zika virus (ZIKV) and the 4 dengue virus (DENV) serotypes are mosquito-borne Flaviviruses that are associated with severe neuronal and hemorrhagic syndromes. The mature flavivirus infectious virion has 90 envelope (E) protein homo-dimers that pack tightly to form a smooth protein coat with icosahedral symmetry. Human antibodies that strongly neutralize ZIKV and DENVs recognize complex quaternary structure epitopes displayed on E-homo-dimers and higher order structures. The ZIKV and DENV E protein expressed as a soluble protein is mainly a monomer that does not display quaternary epitopes, which may explain the modest success with soluble recombinant E (sRecE) as a vaccine and diagnostic antigen. New strategies are needed to design recombinant immunogens that display these critical immune targets. Here we present two novel methods for building or stabilizing in vitro E-protein homo-dimers that display quaternary epitopes. In the first approach we immobilize sRecE to enable subsequent dimer generation. As an alternate method, we describe the use of human mAbs to stabilize homo-dimers in solution. The ability to produce recombinant E protein dimers displaying quaternary structure epitopes is an important advance with applications in flavivirus diagnostics and vaccine development.